SipD and IpaD induce a cross-protection against Shigella and Salmonella infections. - Bakhos Jneid; Audrey Rouaix; Cécile Féraudet-Tarisse; Stéphanie Simon (Public Library of Science (PLoS), 2020)
Salmonella and Shigella species are food- and water-borne pathogens that are responsible for enteric infections in both humans and animals and are still the major cause of morbidity and mortality in the emerging countries. The existence of multiple Salmonella and Shigella serotypes as well as the emergence of strains resistant to antibiotics require the development of broadly protective therapies. Those bacteria utilize a Type III Secretion System (T3SS), necessary for their pathogenicity. The structural proteins composing the T3SS are common to all virulent Salmonella and Shigella spp., particularly the needle-tip proteins SipD (Salmonella) and IpaD (Shigella). We investigated the immunogenicity and protective efficacy of SipD and IpaD administered by intranasal and intragastric routes, in a mouse model of Salmonella enterica serotype Typhimurium (S. Typhimurium) intestinal challenge. Robust IgG (in all immunization routes) and IgA (in intranasal and oral immunization routes) antibody responses were induced against both proteins. Mice immunized with SipD or IpaD were protected against lethal intestinal challenge with S. Typhimurium or Shigella flexneri (100 Lethal Dose 50%). We have shown that SipD and IpaD are able to induce a cross-protection in a murine model of infection by Salmonella and Shigella. We provide the first demonstration that Salmonella and Shigella T3SS SipD and IpaD are promising antigens for the development of a cross-protective Salmonella-Shigella vaccine. These results open the way to the development of cross-protective therapeutic molecules.